Gender Policy Implementation Management - Syamsuddin Maldun (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Studi Islam Sunan Doe, 2022)
Gender issues are explicitly included in all existing government policies as part of Indonesia's goal to realize human rights. This is reflected in NAWACITA's second priority, which aims to increase women's participation and representation in politics and development. NAWACITA's eighth priority also includes the protection of children, women and disadvantaged communities. In this regard, the strategic issues to be addressed in the 2015-2019 development period are: (1) improving the role and quality of life of women in various areas of development; (2) protecting women from various forms of violence, including trafficking in persons (TPPO); (3) gender mainstreaming (PUG) and the institutional capacity of institutions to protect them.